Public transit electrification planning with energy storage via second-life batteries – a stochastic programming approach - Franco, Sergio Edgar; Wang, Jing; Shirkoohi, Majid Gholami; Chen, Qiao; Mérida, Walter (Applied energy, 2025)
As part of decarbonization strategies, public transit systems are aiming to electrify their fleets in response to climate targets and net-zero goals. However, the resulting increase in electricity demand may lead to energy stress on the electrical grid. Second-life batteries (SLBs) offer a potential solution, yet their financial, energy, and environmental impacts remain underexplored, as does the long-term planning for their integration. This study proposes a strategic planning model for transitioning a public transit fleet to battery electric buses (BEBs), incorporating the deployment of SLBs as a battery energy storage system (BESS). The model jointly optimizes decisions on asset procurement, replacement, route-level fleet assignments, the integration of SLBs as BESS, and the installation of a supporting renewable energy system (RES). A multi-period stochastic programming framework is employed to optimize planning under uncertainties, such as vehicle and battery costs, and the model is formulated as a mixed-integer linear program. A case study of Metro Vancouver's transit system is conducted to evaluate three electrification pathways. Results show that SLBs can meet up to 84 % of the fleet's recharging energy demand, reduce annual operating costs by up to $107 million, and lower total system costs by $78 million. A sensitivity analysis of battery and electricity prices provides insights into the integration of SLBs under different market and policy conditions. •Strategic fleet electrification planning via stochastic programming.•Second life batteries integrated as an energy storage system.•A case study based on data from Metro Vancouver, Canada.•Assessment of financial, energy, and environmental impact of second life batteries.